A Buddhist Approach to Peace and Unity among the Multi-ethnic Groups in the Republic of the Union of Myanmar - Aung, Myint; Mahatthanadull, Sanu (Journal of International Buddhist Studies, 2021)
This article is an attempt to present a Buddhist approach to peace and unity among the multi-ethnic groups in the Republic of the Union of Myanmar. Basically, the problematic circumstances of the ethnical groups in Myanmar is ethnic diversity, and no peace. Peace is the way of the Buddha’s teachings to the end of suffering, hatred, and conflict in the mind of individual. The ultimate goal of Buddhism is peace. That is how the Buddhist approach to peace in order to attain the peaceful way and intentions characterize the path of life. This study is focusing on the Buddhist stresses of solving the problem of peace, especially the cause of ethnic diversity and having no peace. The findings show Myanmar’s ethnic conflict is between the majority Burmese and the minority ethnic groups based on diversity and conflict. Do’s and Dont’s of the guide to peace and gave many examples as references in peace. Finally, it is suggested that both Burmese and minority ethnic groups should practice according to Buddhist approach to peace and unity among the multi-ethnic groups in Republic of the Union of Myanmar is the most importance element of the way to peace in Myanmar as well as in the world, that is to follow the three key elements namely: - the Middle Way as a path to make peace, the good government (dhammābhipāla), and living unity and harmony. Therefore, this article is useful for the peace, unity of Myanmar and in the world as well.